2013
DOI: 10.1016/j.ijrobp.2012.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Toxicities Affecting Quality of Life After Chemo-IMRT of Oropharyngeal Cancer: Prospective Study of Patient-Reported, Observer-Rated, and Objective Outcomes

Abstract: Purpose After conventional radiotherapy for head and neck cancer, xerostomia has traditionally been the major effector of patient-reported quality of life (QOL), and recent publications suggest that dysphagia has an even stronger effect. We hypothesized that IMRT aiming to spare the salivary glands and swallowing structures reduced, or eliminated, the effects of these toxicities on QOL. Methods and Materials Prospective longitudinal study: 72 patients with Stage III-IV oropharyngeal cancer treated uniformly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
156
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(169 citation statements)
references
References 20 publications
6
156
1
6
Order By: Relevance
“…More specifically, physiologic impairment quantified from the MBS study has been shown to predict quality of life, and MBS endpoints of aspiration and pharyngeal residue significantly predict post-treatment pneumonia after treatment for OPC (p=0.017, Se 80%, Sp 60%). 36,37 These data offer compelling support for inclusion of instrumental assessment, particularly the MBS, in TORS trials, as the data obtained from MBS cannot be reliably inferred from subjective, self-report of swallowing function obtained from PRO measures.…”
Section: Discussionmentioning
confidence: 92%
“…More specifically, physiologic impairment quantified from the MBS study has been shown to predict quality of life, and MBS endpoints of aspiration and pharyngeal residue significantly predict post-treatment pneumonia after treatment for OPC (p=0.017, Se 80%, Sp 60%). 36,37 These data offer compelling support for inclusion of instrumental assessment, particularly the MBS, in TORS trials, as the data obtained from MBS cannot be reliably inferred from subjective, self-report of swallowing function obtained from PRO measures.…”
Section: Discussionmentioning
confidence: 92%
“…Adjuvant treatment reporting is also critical in outcomes analyses. Surgery with radiation and chemotherapy invariably affect patient function and QOL more than surgery or radiation alone 21,22,28,41 (level 4 evidence). Although pure comparison between modalities may not be feasible, acknowledging the effects of adjuvant treatments have on function and QOL is important.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews in head and neck reconstruction have increased in recent years, but a definitive review of the functional outcomes in reconstruction is lacking 20 (level 3 evidence). Although nonoperative management of head and neck cancers have well-designed, single-institution studies as well as systematic review to assess functional outcomes 21,22 (level 3 evidence), such rigor in examining the role of reconstruction in the operative management of this disease has not been employed. We asked the following question to guide our systematic review: what are the functional outcomes of head and neck reconstruction involving the oral cavity and oropharynx?…”
Section: Functional Outcomes In Reconstruction Of the Oral Cavity Andmentioning
confidence: 99%
“…Dysfunction of the swallowing structures is a common cause of severe acute and late toxicity after head and neck radiotherapy and is perhaps the strongest determinant of long-term quality of life in HNC survivors (Hunter et al 2013 ;Langendijk et al 2008 ;Machtay et al 2008 ;Terrell et al 2004 ). Radiotherapy dose to the swallowing structures, specifi cally the pharyngeal constrictor (PC) muscles, has been implicated as a primary treatment-related predictor of swallowing dysfunction after chemoradiotherapy (Eisbruch et al 2011 ;Popovtzer et al 2009 ).…”
Section: Preservation Of the Swallowing Structuresmentioning
confidence: 99%